2005
DOI: 10.1086/430520
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Heights of the Sources of Solar Ultraviolet Emission Lines in a Quiet-Sun Region

Abstract: The radiance and Doppler-velocity maps of the emission lines of Si ii, C iv, and Ne viii obtained in a quiet region of the Sun by SUMER (Solar Ultraviolet Measurements of Emitted Radiation) are correlated with the vertical component, , of the magnetic field vector as extrapolated, by means of a force-free field model, from B z the photospheric magnetic field measured by MDI (Michelson Doppler Imager). It is found that, with increasing vertical height, each of the correlation coefficients initially increases to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(92 citation statements)
references
References 16 publications
12
80
0
Order By: Relevance
“…Thus, the plasma may locally satisfy the condition of β < 1 and the force-free assumption is met approximatively, which, however, is a problem worthy to investigate continually. Some authors have assumed the force-free requirement is satisfied in the quiet Sun and used LFF field extrapolation to study the properties of magnetic field in the quiet Sun (e.g., Tu et al, 2005;Régnier et al 2008 andZhao et al, 2009). In our work, we also assume that the force-free requirement is satisfied in the quiet Sun and attempt to apply the NLFF magnetic field extrapolation to the quiet Sun.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the plasma may locally satisfy the condition of β < 1 and the force-free assumption is met approximatively, which, however, is a problem worthy to investigate continually. Some authors have assumed the force-free requirement is satisfied in the quiet Sun and used LFF field extrapolation to study the properties of magnetic field in the quiet Sun (e.g., Tu et al, 2005;Régnier et al 2008 andZhao et al, 2009). In our work, we also assume that the force-free requirement is satisfied in the quiet Sun and attempt to apply the NLFF magnetic field extrapolation to the quiet Sun.…”
Section: Discussionmentioning
confidence: 99%
“…Régnier et al (2008) used the magnetic field extrapolation to derive the null points density in the quiet Sun. Tu et al (2005) used the magnetic field extrapolation to study the origin of solar wind and give the 3D structure of magnetic field in a quiet Sun. They found that there is no canopy shape as originally suggested, but the cross section of magnetic flux increases almost linearly with height.…”
Section: Introductionmentioning
confidence: 99%
“…They originate from small-scale bright regions, often preceded by footpoint brightenings. Tian et al (2014) concluded that the existence of network jets are consistent with the 'Magnetic Furnace Model' of solar wind (Axford and McKenzie, 1992;Tu et al, 2005;Yang et al, 2013) and thus may serve as strong candidates for supply of mass and energy to the solar wind and corona. Tian et al (2014) also suggest that some of these network jets may be the on-disk counterparts and TR manifestations of the chromospheric type-II spicules (see also Pereira et al (2014) The network jets in CHs, as reported in Tian et al (2014), have widths of 300 km with lifetimes of 20-80 s and lengths of 4-10 Mm.…”
Section: Introductionmentioning
confidence: 90%
“…Above the chromospheric network, the outflow appears to be strongest in the dark regions of the coronal holes and not in the bright polar plumes Patsourakos and Vial 2000). Wiegelmann et al (2005) and Tu et al (2005aTu et al ( , 2005b identified the locales of strong blue shifts as the footpoint regions of funnels in coronal holes. An observation of a small plume in an equatorial coronal hole has been reported by Del Zanna and Bromage (1999).…”
Section: Coronal Holes Polar Plumes and The Fast Solar Windmentioning
confidence: 99%